Scaling up the "24/7 BHU" strategy to provide round-the-clock maternity care in Punjab, Pakistan: a theory-driven, coproduced implementation study - Sarah Salway; Zubia Mumtaz; Afshan Bhatti; Amy Barnes; Jeremy Dawson; Gian Singh Jhangri (BMC, 2022)
Abstract Background Pakistan's maternal mortality rate remains persistently high at 186/100,000 live births. The country's government-run first-level healthcare facilities, the basic health units (BHUs), are an important source of maternity care for rural women. However,BHUsonly operate on working days from 8:00 am to 2:00 pm. Recognizing that this severely constrains access to maternity services, the government is implementing the "24/7 BHU" initiative to upgrade BHUs to provide round-the-clock care. Although based on a successful pilot project, initial reports reveal challenges in scaling up the initiative. This implementation research project aims to address a key concern of the Government of Punjab: How can the 24/7 BHU initiative be successfully implemented at scale to provide high-quality, round-the-clock skilled maternity care in rural Punjab? Methods The project consists of two overlapping work packages (WP). WP1 includes three modules generating data at the directorate, district and BHU levels. Module 1 uses document analysis and policy-maker interviews to explicateprogrammetheory and begin to build a system model. Module 2 compares government-collected data with data generated from a survey of 1500 births to assess BHU performance. Module 3 uses institutional ethnographies in 4-5 BHUs in three districts to provide a detailed system for understanding and identifying processes that influence scale-up. WP2 includes two modules. First, two workshops and regular meetings with stakeholders integrate WP1 findings, identify feasible changes and establish priorities. Next, "change ideas" are selected for testing in one district and 2-3 BHUs through carefully documented pilots using the PDSA (plan-do-study-act) improvement approach. An integrated knowledge translation approach will engage key policy and practice stakeholders throughout the project. Discussion This theory-driven implementation research project willcoproducesignificant new understandings of the wider system in which the 24/7 BHU initiative is being implemented, and actionable knowledge that will highlight ways the implementation processes might be modified to enable BHUs to meet service provision goals. This study will also produce insights that will be relevant for other South Asian and low- and middle-income countries (LMICs) that experience similar challenges of programme scale-up and delivery of maternal health services to remote and marginalized communities.